Karakteristik dan Tingkat Pengetahuan Ibu Hamil dengan Kejadian Kurang Energi Kronis (KEK) - Sulistianingrum, Lely (Universitas Malahayati Bandar Lampung, 2023)
Background: Chronic energy deficiency (CED) in pregnancy is a nutrition problem in Indonesia. The contribution and occurrence of SEZ in pregnant women will affect fetal growth and development. Pregnant women with nutrition and health problems have an impact on the health and safety of mothers and babies and the quality of babies born. The causes of the high prevalence of SEZ that are most often found in the community are behavioral factors such as lifestyle, eating patterns, and socioeconomic factors. Objective: to determine the analysis of factors associated with the incidence of SEZ in pregnant women at the Way Kandis Health Center, Bandar Lampung City in 2023. Method: This type of research is quantitative with cross sectional design. The population in this study were all pregnant women at the Way Kandis Health Center in Bandar Lampung. The sample was 70 respondents. The sampling technique used purposive sampling technique. Data were collected with a questionnaire sheet consisting of 15 questions, including the sub-theories of the definition of SEZ, signs and symptoms, how to identify pregnant women with SEZ, early detection of SEZ and prevention. Data collection included editing, scoring, coding, and tabulating, then data were analyzed by univariate and bivariate analysis manually with computer. Results: The results showed that there was a relationship between parity and the incidence of SEZ in pregnant women with a p value of 0.001 <0.05, education with the incidence of SEZ with a p value of 0.014 <0.05 and the level of knowledge of pregnant women with a p value of 0.047 <0.05. Conclusion: there is a relationship between maternal characteristics (parity and education) and the level of maternal knowledge with the incidence of SEZ at Way Kandis Health Center, Bandar Lampung City in 2023. Suggestion: It is hoped that there will be an increase in socialization about Chronic Energy Deficiency (SEZ) in pregnant women, and as a consideration for puskesmas, especially in determining programs that support the reduction in the percentage of achievements of pregnant women with SEZ. Keywords: Pregnant women, Chronic Energy Deficiency, Malnutrition